Medial Clavicular Osteophyte: A Novel Cause of Paget-Schroetter Syndrome - Keagan Werner-Gibbings; Steven Dubenec (Case Reports in Vascular Medicine)
Paget-Schroetter syndrome is a form of upper limb deep venous thrombosis usually seen in younger patients in association with repetitive activities of the affected limb. When occurring in more elderly patients or in those where it is difficult to appreciate a causative mechanism, other aetiologies should be considered. We present a case in which degenerative osteoarthritis of the sternoclavicular joint with osteophyte development impinged on the subclavian vein, leading to extensive upper limb thrombosis. The difficulties in identifying and managing this unusual cause of Paget-Schroetter are presented and discussed.